Pengaruh Reward dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Wisma Bangun Persada di Jakarta Tahun 2024 - Sumidartiny, Ai Netty; Nurhadi Ningsih, Yuliana (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to determine the impact of rewards and work discipline towards employee performance at PT. Wisma Bangun Persada in Jakarta in 2024. This research used a descriptive quantitative approach with the Purposive Sampling technique. Data collection technique used a questionnaire in the form of questions with a sample of 60 respondents who are employees of PT. Wisma Bangun Persada. The results of this research indicate that there are a positive and significant partial influence between Reward (X1) on Employee Performance (Y) by contributing 47.5% and Work Discipline (X2) contributing 63.9% to Employee Performance (Y), and Reward and Work Discipline simultaneously affect Employee Performance by 65.5%. While the remaining 34.5% is influenced by other variables which were not examined in this research.